Working as Scientist and Engineer: A Strategy for Empowering Critical Thinking Skills through the STEM-EDP Learning Design - Ramli, Murni; Sholikhah, Salma Majid Fadhilatus; Ariani, Sri Retno Dwi; Zahro, Ani Satun (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
STEM (Science, technology, Engineering, and Mathematics)-based learning has evolved into an instructional design that accommodates the integration of disciplines to understand properly scientific phenomena. To explain scientific phenomena, students need to imitate the work of scientist and engineer who apply the critical thinking skills (CTS). Hence, this study aims to prove the impact of learning design based on the STEM approach to empower the CTS. The learning follows the steps of the Engineering Design Process (EDP), and the assigned STEM project was a robotic hand inspired by traditional Javanese puppets called Wayang. The learning setup relates to the topics of the 8th-grade science curriculum, i.e. body movement system. A pre-experimental design using a one-shot case pretest-posttest design was applied to a single experimental class. The sample was purposefully selected, consisting of all students in class 8A at Public Junior High School 4 Surakarta (N=30). Data collection involved assessing CTS using pretests and posttests. Based on the paired t-test, the results indicate an improvement in students' critical thinking skills, marked by an increasing in CTS scores at the pretest (M = 53.87, SD = 16.783) to post-test scores (M = 82.63, SD = 16.486), with the significant result, sig < α, 0.049 < 0.05, indicating the rejection of H0. This study concludes that the STEM-EDP learning design has a positive impact on the critical thinking skills of 8th-grade students.